The Relationship between Taking Drugs and the Incidence of Gout Arthritis in the Elderly in Tunggulo Village, West Limboto District, Gorontalo Regency - Astri Nikmatul Riska Pomide; Rosmin Ilham; Hamna Vonny Lasanuddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The Relationship between Taking Drugs and the Incidence of Gout Arthritis in the Elderly in Tunggulo Village, West Limboto District, Gorontalo Regency. Thesis. Nursing Study Program, Faculty of Health Sciences, University of Muhammadiyah Gorontalo.Supervised by Rosmin Ilham as the chairman, and as a Member of Hamna Vonny Lasanuddin. Gout arthritis is a degenerative disease that is often experienced by the elderly and can be affected by long-term drug consumption. The elderly generally experience various comorbidities so they are at risk of using many types of drugs that can increase uric acid levels. This study aims to determine the relationship between drug consumption and the incidence of gout arthritis in the elderly in Tunggulo Village, West Limboto District, Gorontalo Regency. This study uses a quantitative method with a cross sectional design. The sample totaled 78 respondents who were selected using the purposive sampling technique. Data was collected through questionnaires and analyzed using the Chi-Square test. The results of the study showed that most of the elderly have a high risk of taking drugs and experiencing the incidence of gout arthritis. Bivariate analysis showed that there was a significant relationship between drug consumption and the incidence of gout arthritis (p < 0.001).